(untitled) (Research, Society and Development, 2022)
The present work presents the cut of a Master’s dissertation, developed in the Graduate Program in Teaching Exact Sciences - PPGECE, of the University of Vale do Taquari - Univates. Therefore, this paper aims to approach a practice developed with students from two third year classes of Normal High School, from a public school in the State of Rio Grande do Sul. During the practice, we approach concepts related to Experimentation, Scientific Literacy and Active Methodologies, for Science Teaching in the Initial Years of Elementary School. The methodology used was based on the concepts of qualitative research with approaches to the case study. We can see, among the results found, that students and future teachers established relationships between the terms studied, in addition to experiencing a practice based on Active Methodologies (Inverted Classroom), favoring curiosity, creativity and group work.